Appendiceal Mucinous Neoplasms: Diagnosis and Management. (29th June 2017) - Shaib, Walid L.; Assi, Rita; Shamseddine, Ali; Alese, Olatunji B.; Staley, Charles; Memis, Bahar; Adsay, Volkan; Bekaii‐Saab, Tanios; El‐Rayes, Bassel F.
Abstract : Objective: Appendiceal mucinous neoplasms (AMNs) are a rare and heterogeneous disease for which clinical management is challenging. We aim to review the literature regarding modalities of treatment to guide the management of AMNs. Methods and Review Criteria: We conducted a PubMed search in February 2016 for English‐language publications, using the terms "appendiceal, " "appendix, " "carcinoma, " "cancer, " "mucinous, " "treatment, " "genes, " "target, " "genomic, " and terms listed in the articles' subheadings. Published reports and abstracts from the American Society of Clinical Oncology meetings were also searched. Results: In this review, we summarize current data and controversies in AMN classification, clinical presentation, molecular alterations, treatment outcomes with regard to cytoreductive surgery, hyperthermic intraperitoneal chemotherapy (HIPEC), and the role of systemic chemotherapy. Conclusion: Appendiceal mucinous neoplasms are a heterogeneous group of tumors with a rising incidence. Treatment is based on stage and histology. Low‐grade tumors are treated surgically with resection of the primary site in early stage disease, or peritoneal debulking and HIPEC in patients with advanced stage disease. Treatment of high‐grade tumors requires further prospective trials, and options include debulking surgery and HIPEC with or without preoperative chemotherapy. Trials evaluating novel therapies based on the molecular profiling of AMN tumors are needed to evaluate therapeutic options in patients who are not surgical candidates. Abstract : Appendiceal mucinous neoplasms are rare and challenging to manage. This review summarizes the current literature and controversies in classification, clinical presentation, molecular alterations, and treatment outcomes in this heterogeneous group of tumors and provides guidelines for treatment.